Barriers to Social Integration for People with Disabilities. The Polish Experiences - Twardowski, Andrzej (Wydawnictwo Naukowe UAM, 2014)
The implementation of social integration consists in creating opportunities for the disabled to participate in normal life, providing access to all public institutions and social situations in which fully able people participate. Social integration in this meaning is a long way and numerous barriers are likely to appear. Barriers are all obstacles which make it difficult or impossible for the disabled to participate in the mainstream of social life and to perform socially appreciated roles. The author discusses main social integration barriers of persons with disabilities in Poland: diagnostic, educational, social, psychological, and employment-related.
Bariery integracji społecznej osób z niepełnosprawnościami. Polskie doświadczenia
Keywords: social integration; people with disabilities; barriers to integration